The way we work : getting to know the amazing human body - Macaulay, David; Walker, Richard, 1951- (Boston : Houghton Mifflin, 2008)
A visual exploration of the inner workings of the human body that uses close-ups, cross-sections, and perspectives to look at the different body systems and how they function.
"Walter Lorraine books.".
Includes index.
Booklist.
Pub Weekly.
School Library Journal starred.
8.2
Keywords: Human body -- Juvenile literature; Human physiology -- Juvenile literature; Human body; Human physiology; Human body; Physiology